Method for robust enhancement of P2P network - Hao ZHAO; Wei LIN; Shengli LIU (网络与信息安全学报)
With the widespread use of the Internet,the stability of network communication management architecture and service provision has become increasingly important.A P2P network model based on neighbor-neighbor lists was constructed,and two algorithms(network repairing and pruning) were proposed to improve the reliability and robustness of the network structure.Simulation experiments show that the proposed model and algorithm can effectively improve the self-healing of P2P networks under given threat conditions.